Military Service Members with Major Lower Extremity Fractures Return to Running with a Passive-dynamic Ankle-foot Orthosis: Comparison with a Normative Population. Issue 11 (8th November 2021) - Peterson, Shian Liu; Kingsbury, Trevor D.; Djafar, Tatiana; Stewart, Julianne; Kuhn, Kevin M.
Abstract: Background: Lower extremity fractures represent a high percentage of reported injuries in the United States military and can devastate a service member's career. A passive dynamic ankle-foot orthosis (PD-AFO) with a specialized rehabilitation program was initially designed to treat military service members after complex battlefield lower extremity injuries, returning a select group of motivated individuals back to running. For high-demand users of the PD-AFO, the spatiotemporal gait parameters, agility, and quality of life is not fully understood with respect to uninjured runners. Questions/purposes: Do patients who sustained a lower extremity fracture using a PD-AFO with a specialized rehabilitation program differ from uninjured service members acting as controls, as measured by (1) time-distance and biomechanical parameters associated with running, (2) agility testing (using the Comprehensive High-level Activity Mobility Predictor performance test and Four Square Step Test), and (3) the Short Musculoskeletal Function Assessment score. Methods: We conducted a retrospective data analysis of a longitudinally collected data registry of patients using a PD-AFO from 2015 to 2017 at a single institution. The specific study cohort were patients with a unilateral lower extremity fracture who used the PD-AFO for running. Patients had to be fit with a PD-AFO, have completed rehabilitation, and have undergone a three-dimensional (3-D) running analysis at a self-selected speed at the completion of the program. Of the 90 patients who used the PD-AFO for various reasons, 10 male service members with lower extremity fractures who used a PD-AFO for running (median [range] age 29 years [22 to 41], height 1.8 meters [1.7 to 1.9], weight 91.6 kg [70 to 112]) were compared with 15 uninjured male runners in the military (median age 33 years [21 to 42], height 1.8 meters [1.7 to 1.9], weight 81.6 kg [71.2 to 98.9]). The uninjured runners were active-duty service members who voluntarily participated in a gait analysis at their own self-selected running speeds; to meet eligibility for inclusion as an uninjured control, the members had to be fit for full duty without any medical restrictions, and they had to be able to run 5 miles. The controls were then matched to the study group by age, weight, and height. The primary study outcome variables were the running time-distance parameters and frontal and sagittal plane kinematics of the trunk and pelvis during running. The Four Square Step Test, Comprehensive High-level Activity Mobility Predictor scores, and Short Musculoskeletal Function Assessment scores were analyzed for all groups as secondary outcomes. Nonparametric analyses were performed to determine differences between the two groups at p < 0.05. Results: For the primary outcome, patients with a PD-AFO exhibited no differences compared with uninjured runners in median (range) running velocity (3.9 meters/second [3.4 to 4.2] versus 4.1 meters/second [3.1 to 4.8], median difference 0.2; p = 0.69), cadence (179 steps/minute [169 to 186] versus 173 steps/minute [159 to 191], median difference 5.8; p = 0.43), stride length (2.6 meters [2.4 to 2.9] versus 2.8 meters [2.3 to 3.3], median difference 0.2; p = 0.23), or sagittal plane parameters such as peak pelvic tilt (24° [15° to 33°] versus 22° [14° to 28°], median difference 1.6°; p = 0.43) and trunk forward flexion (16.2° [7.3° to 23°) versus 15.4° [4.2° to 21°), median difference 0.8°; p > 0.99) with the numbers available. For the secondary outcomes, runners with a PD-AFO performed worse in Comprehensive High-level Activity Mobility Predictor performance testing than uninjured runners did, with their four scores demonstrating a median (range) single-limb stance of 35 seconds (32 to 58) versus 60 seconds (60 to 60) (median difference 25 seconds; p < 0.001), t-test result of 15 seconds (13 to 20) versus 13 seconds (10 to 14) (median difference 2 seconds; p < 0.001), and Illinois Agility Test result of 22 seconds (20 to 25) versus 18 seconds (16 to 20) (median difference 4; p < 0.001). Edgren side step test result of 20 meters (16 to 26) versus 24 meters (16 to 29) (median difference 4 meters; p = 0.11) and the Four Square Step Test of 5.5 seconds (4.1 to 7.2) versus 4.2 seconds (3.1 to 7.3) (median difference 1.3 seconds; p = 0.39) were not different between the groups with an effect size of 0.83 and 0.75, respectively. Conclusion: The results of our study demonstrate that service members run with discernible differences in high-level mobility and demonstrate inferior self-reported patient functioning while having no differences in speed and biomechanics compared with their noninjured counterparts with the sample size available. This study is an early report on functional gains of highly motivated service members with major lower extremity injuries who use a PD-AFO and formalized therapy program to run. Level of Evidence: Level III, therapeutic study.